Дослідження тестувань на проникнення та безпеки веб-додатків - Зеггум Суфіан (My University, 2023)
The object of research is the process of detecting vulnerabilities and protecting web applications against them. The subject of the research is methods of testing and detecting vulnerabilities of web applications. The purpose of the work is the analysis of the most common types of attacks on web applications, the analysis of existing methods of testing web applications to identify vulnerabilities, and recommendations for the protection of web applications. Research methods – empirical analysis, comparison. Today, the topic of protecting web applications is relevant, because nowadays people's lives cannot be imagined without the use of web applications. This qualification work analyzes the most common current types of threats and vulnerabilities of web applications. Methods that allow testing of web applications to detect possible vulnerabilities are considered. An analysis of modern methods of protecting web applications has been carried out. Simulations using the Damn Vulnerable Web Application (DVWA) framework are performed and recommendations are provided for the use of web application protection methods.
Keywords: Information Security; Threats; Vulnerabilities; Web Applications; Security Risks; Scanning; Penetration Testing